EM23, A Natural Sesquiterpene Lactone from Elephantopus mollis, Induces Apoptosis in Human Myeloid Leukemia Cells through Thioredoxin- and Reactive Oxygen Species-Mediated Signaling Pathways - Li, Hongyu; Li, Manmei; Wang, Guocai; Shao, Fangyuan; Chen, Wenbo; Xia, Chao; Wang, Sheng; Li, Yaolan; Zhou, Guangxiong; Liu, Zhong (Frontiers in Pharmacology, 2016)
Elephantopus mollis H.B.K. (EM) is a traditional herbal medicine with multiple pharmacological activities. However, the efficacy of EM in treating human leukemia is currently unknown. In the current study, we report that EM23, a natural sesquiterpene lactone isolated from EM, inhibits the proliferation of human chronic myeloid leukemia K562 cells and acute myeloid leukemia HL-60 cells by inducing apoptosis. Translocation of membrane-associated phospholipid phosphatidylserines, changes in cell morphology, activation of caspases and cleavage of PARP were concomitant with this inhibition. The involvement of the mitochondrial pathway in EM23-mediated apoptosis was suggested by observed disruptions in mitochondrial membrane potential (MMP). Mechanistic studies indicated that EM23 caused a marked increase in the level of reactive oxygen species (ROS). Pretreatment with N-acetyl-L-cysteine (NAC), a ROS scavenger, almost fully reversed EM23-mediated apoptosis. In EM23-treated cells, the expression levels of thioredoxin (Trx) and thioredoxinreductase (TrxR), two components of the Trx system involved in maintaining cellular redox homeostasis, were significantly down-regulated. Concomitantly, Trx regulated the activation of apoptosis signal-regulating kinase 1 (ASK1) and its downstream regulatory targets, the p38, JNK, and ERK MAPKs. EM23-mediated activation of ASK1/MAPKs was significantly inhibited in the presence of NAC. Furthermore, tumor necrosis factor alpha (TNF-α)-mediated activation of nuclear factor-κB (NF-κB) was suppressed by EM23, as suggested by the observed blockage of p65 nuclear translocation, phosphorylation and reversion of IκBα degradation following EM23 treatment. Taken together, these results provide important insights into the anticancer activities of the EM component EM23 against human chronic myeloid leukemia K562 cells and acute myeloid leukemia HL-60 cells.